From revolution to power in Brazil : how radical leftists embraced capitalism and struggled with leadership - Serbin, Kenneth P. (Kellogg Institute series on democracy and development., 2019)
"From Revolution to Power in Brazil: How Radical Leftists Embraced Capitalism and Struggled with Leadership examines terrorism from a new angle. Kenneth Serbin portrays a generation of Brazilian resistance fighters and militants struggling to rebuild their lives after suffering torture and military defeat by the harsh dictatorship that took control with the support of the United States in 1964, exiting in 1985. Based on two decades of research and more than three hundred hours of interviews with former members of the revolutionary organization National Liberating Action, Serbin's is the first book to bring the story of Brazil's long night of dictatorship into the present. It explores Brazil's status as an emerging global capitalist giant and its unique contributions and challenges in the social arena"--